2009
DOI: 10.1063/1.3073842
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependence of structure and magnetic properties of annealed [Fe/Pt]n multilayer films

Abstract: The L10 FePt phase material has potential applications for magnetic recording and permanent magnets due to its high magnetocrystalline anisotropy energy density. The heat treatment of [Fe/Pt]n multilayer films is one approach to form the L10 FePt phase at a lower processing temperature, which is highly desirable for its applications. This paper reports the influence of film total thickness (8–100 nm) on the structure and magnetic properties of annealed [Fe/Pt]n multilayer films. A novel technique based on holl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…% for B and C, and > 10.5 at. % for B and E) The source of this difference in the transformation enthalpy for films C and D may be the diffusion of Fe into Pt to form the A1 FePt phase, [80][81][82][83][84][85] but occurring such that the calorimetry experiments are not able to directly measure the heat release associated with this diffusion, but can detect the "missing" heat. This diffusion occurs at all interfaces, but its impact on the measured enthalpy is magnified when more interfaces are present as has been seen in Ni/Al multilayer films where the diffusion region was estimated to be 4 nm thick.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…% for B and C, and > 10.5 at. % for B and E) The source of this difference in the transformation enthalpy for films C and D may be the diffusion of Fe into Pt to form the A1 FePt phase, [80][81][82][83][84][85] but occurring such that the calorimetry experiments are not able to directly measure the heat release associated with this diffusion, but can detect the "missing" heat. This diffusion occurs at all interfaces, but its impact on the measured enthalpy is magnified when more interfaces are present as has been seen in Ni/Al multilayer films where the diffusion region was estimated to be 4 nm thick.…”
Section: Resultsmentioning
confidence: 99%
“…The solid solution phase considered was (cFe,Pt), i.e., the face centered cubic, or A1 FePt, 60 which has been previously reported for annealed, sputter deposited Fe/Pt multilayers and for ball milled Fe-Pt samples. [80][81][82][83][84][85] The phases present at each stage of reaction are listed in Table II. To determine the volume percents of the phases present in the films annealed to the highest annealing temperature (725 C), the XRD intensities were corrected using the Lorentz, polarization, and Debye Waller factors in addition to a sample size correction factor, as detailed elsewhere. 86 The XRD patterns showed that the phases were 111 h i fiber-textured.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, magnetic L1 1 CoPt and L1 0 FePt nanocrystalline and metastable alloys have been prepared from Co/Pt [406] and Fe/Pt [402,[407][408][409] systems, respectively, while TiNi alloys have been obtained from Ti/Ni multilayers [133,410]. The fast formation of ordered phases was made possible due to the existance of shorter diffusion paths between the coupled metals, which were made available by using individual layer thicknesses in the order of only a few nanometers (0.2-3 nm) [405,408,409,411].…”
Section: Nano Multilayers As Precursors For the Synthesis Of Amorphou...mentioning
confidence: 99%